2019
DOI: 10.1177/1744806919842961
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-stimulated adenylyl cyclase subtype 1 is required for presynaptic long-term potentiation in the insular cortex of adult mice

Abstract: Recent studies indicate that presynaptic long-term potentiation in the anterior cingulate cortex may contribute to chronic pain-related anxiety. In addition to the anterior cingulate cortex, the insular cortex has also been indicated in chronic pain and its related emotional disorders. In the present study, we used a 64-channel multielectrode dish (MED64) system to record pre-long-term potentiation in the insular cortex. We showed that low-frequency stimulation paired with a GluK1-containing kainate receptor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 34 publications
3
19
0
Order By: Relevance
“…For signaling pathways, the results demonstrated that neuronal AC1 is important for CGRP produced presynaptic enhancement. Previous studies demonstrate that AC1 is cortical for both pre-and post-LTP in the ACC and IC [29,32,38]. These results further support the important roles of AC1 in presynaptic potentiation within cortical synapses.…”
Section: Innervation and Distribution Of Cgrp In The Icsupporting
confidence: 78%
“…For signaling pathways, the results demonstrated that neuronal AC1 is important for CGRP produced presynaptic enhancement. Previous studies demonstrate that AC1 is cortical for both pre-and post-LTP in the ACC and IC [29,32,38]. These results further support the important roles of AC1 in presynaptic potentiation within cortical synapses.…”
Section: Innervation and Distribution Of Cgrp In The Icsupporting
confidence: 78%
“…For signaling pathways, we have demonstrated that neuronal AC1 is important for CGRP produced presynaptic enhancement. Previous studies demonstrate that AC1 is cortical for both pre-and post-LTP in the ACC and IC [26,29,34]. These results further support the important roles of AC1 in presynaptic potentiation within cortical synapses.…”
Section: Modulation Of Synaptic Transmission By Cgrp In the Icsupporting
confidence: 78%
“…In light of these, pre-LTP is thought to mediates anxiety signals triggered by chronic pain, while post-LTP is related to behavioral hyperalgesia during chronic pain [57]. In a recent study, Zhuo M et al succeeded in recording pre-LTP in the insular cortex, which shared similar molecular mechanisms with ACC pre-LTP [58]. In the present study, we observed an increase in presynaptic glutamate release within aIC, suggesting the possibility of the existence of insular pre-LTP during painful CP.…”
Section: Discussionmentioning
confidence: 99%